MEDIA INFORMASI VIRTUAL REALITY UNTUK MEMPROMOSIKAN SEKOLAH DI MASA PANDEMI - Andik Prakasa Hadi; Setiyo Adi Nugroho; Agus Priyadi; Rizky Ridwan Saputra (STEKOM PRESS, 2023)
School promotions were carried out directly by visiting junior high schools, during a pandemic this can’t be done. In an effort to attract prospective new students at SMK PGRI 2 Salatiga, it is necessary to innovate by adding promotional media that can be accessed by the wider community. Information distribution can be done through social media and the school's YouTube channel. Information media was chosen as virtual reality in the form of 360° videos to display school facilities and privileges. The measurement indicators used in this study are behavior, interactivity, and sound to find out whether the virtual environment can affect the interest of prospective students at SMK PGRI 2 Salatiga. In addition, the interactivity of the video when it is played and the sound of the environment in the video can give immersive in a school environment. The results of this study by the majority of respondents stated that promotional media virtual reality in the form of 360° videos is appropriate for use for school promotions during a pandemic, as an effort to increase the number of new students.